A Drug–Perfluorocarbon Nanoemulsion with an Ultrathin Silica Coating for the Synergistic Effect of Chemotherapy and Ablation by High‐Intensity Focused Ultrasound. (16th September 2014) - Ma, Ming; Xu, Huixiong; Chen, Hangrong; Jia, Xiaoqing; Zhang, Kun; Wang, Qi; Zheng, Shuguang; Wu, Rong; Yao, Minghua; Cai, Xiaojun; Li, Faqi; Shi, Jianlin
<x xml:space="preserve">Abstract</x> The synergistic effect of chemotherapy and ablation using high‐intensity focused ultrasound (HIFU) is realized with a newly developed drug‐delivery system. The system comprises an ultrathin silica shell surrounding a poly(lactic‐co‐glycolic acid) nanoemulsion core containing the drug (CPT) and a perfluorocarbon (PFOB). This nanosystem presents many advantages in drug delivery, such as excellent structural stability, high drug‐loading capacity, and rapid HIFU‐mediated drug release. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>